Transport disadvantage, social exclusion, and subjective well-being: The role of the neighborhood environment—evidence from Sydney, Australia - Liang Ma; Jennifer Kent; Corinne Mulley (Journal of Transport and Land Use)
This study explores the effects of the neighborhood environment on transport disadvantage, social exclusion, personal health and subjective wellbeing (SWB) using survey data collected in Sydney, Australia. The data is analyzed using structural equation modelling (SEM). Overall, our model supports the hypothesis that a walkable neighborhood environment helps to reduce transport disadvantage and increase social inclusion. Neighborhood density has negative effects on both physical and mental health, but a positive effect on SWB. Further, a cohesive neighborhood environment is associated with less transport disadvantage, more engagement in political and civic activities, more social help, better mental health and higher SWB. By contrast, perception of crime in a neighborhood is associated with more transport disadvantage and worse physical health. Neighborhood aesthetics and the neighborhood social environment have stronger effects on SWB than other neighborhood environment characteristics.